2018
DOI: 10.1016/j.ebiom.2018.05.036
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Depressant Fluoxetine Reveals its Therapeutic Effect Via Astrocytes

Abstract: Although psychotropic drugs act on neurons and glial cells, how glia respond, and whether glial responses are involved in therapeutic effects are poorly understood. Here, we show that fluoxetine (FLX), an anti-depressant, mediates its anti-depressive effect by increasing the gliotransmission of ATP. FLX increased ATP exocytosis via vesicular nucleotide transporter (VNUT). FLX-induced anti-depressive behavior was decreased in astrocyte-selective VNUT-knockout mice or when VNUT was deleted in mice, but it was in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
61
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(62 citation statements)
references
References 71 publications
1
61
0
Order By: Relevance
“…Therapeutic effects of antidepressants on MDD by modulation of astrocytic function (such as producing BDNF and GDNF) have been reported [3639]. Though animal and clinical studies on MDD showed increased BDNF with n-3 PUFA treatment [4042], the relevant cell types were not delineated.…”
Section: Resultsmentioning
confidence: 99%
“…Therapeutic effects of antidepressants on MDD by modulation of astrocytic function (such as producing BDNF and GDNF) have been reported [3639]. Though animal and clinical studies on MDD showed increased BDNF with n-3 PUFA treatment [4042], the relevant cell types were not delineated.…”
Section: Resultsmentioning
confidence: 99%
“…Conventional KO and conditioned astrocytic KO of the calcium homeostasis modulator 2 channel (Calhm2) initiated depression-like behaviors in mice (TST and FST), indicating that this channel is the exit pathway for the release of ATP (Jun et al, 2018). In partial disagreement with these findings, the effect of the antidepressant drug fluoxetine has been shown to increase ATP exocytosis (Kinoshita et al, 2018). In consequence, the authors of this latter study concluded that the astrocytic release of ATP involved in depression operates by vesicular exocytosis rather than by Calhm2 opening.…”
Section: Inhibited Astrocytic Atp Release In the Prefrontal Cortex Anmentioning
confidence: 99%
“…Additional mechanisms, including the possible involvement of A2A receptors in metabolism and neuroinflammation and the role of neurochemical mediators of antidepressant responses, have been considered [22]. For example, it has been shown that fluoxetine-induced upregulation of the Brain-Derived Neurotrophic Factor (BDNF), involved in depression pathophysiology [49], may be mediated by both P1 and P2 receptor signaling [50].…”
Section: Adenosine and Depressionmentioning
confidence: 99%